An analysis of the primary and secondary housing market in Poland: evidence from the 17 largest cities. Issue 2 (3rd July 2017) - Leszczyński, Robert; Olszewski, Krzysztof
ABSTRACT: We analyse the determinants of prices of flats that are bought on the primary (new construction) and secondary markets (existing stock) in the 17 largest cities in Poland during the 2002–2015 period. We find that prices are driven by economic fundamentals, such as income growth and drop in the unemployment or real interest rate. Interestingly, prices in the secondary market react strongly to those fundamentals than to prices in the primary market. Especially, the reaction to the real interest rate is more than twice as high. The most likely buyers on the secondary market are first-time buyers with little own capital, and need a large mortgage. On the other hand, those who buy housing in the primary market quite often sell their old flat, so they only need to acquire the difference. Our finding indicates that the primary and secondary markets need to be analysed separately.